Effect of Probiotic Bacillus megaterium PTB 1.4 on the Population of Intestinal Microflora, Digestive Enzyme Activity and the Growth of Catfish (Clarias sp.) - Wahyu Afrilasari; . Widanarni; Anja Meryandini (Bogor Agricultural University, Indonesia, 2016)
This study aimed to analyze the effect of Bacillus megaterium PTB 1.4 on the population of intestinal microflora, digestive enzyme activity, and the growth of catfish. Gnotobiotic and normal fish were used. Treatment using gnotobiotic was divided into gnoto (with feed and 100 μg/mL rifampicin) and gnotoplus (with feed, 100 μg/mL rifampicin, and 1% probiotic); whereas treatment using normal fish was divided into normalplus (with feed and 1% probiotic) and normal (only feed). The amount of bacteria on gastrointestinal tract was measured 30 days after treatments using the total plate count method. The results indicated no significant difference in bacterial growth between gnotobiotic and normal fish. The total amount of probiotic bacteria with normalplus treatment was significantly different with gnotoplus. The activity of protease and amylase enzymes, and specific growth rate in normalplus treatment were significantly higher (p < 0.05) than other treatments. Bacillus megaterium PTB 1.4 increased the activity of digestive enzymes and the growth of catfish.